Maize-Nutrient-Manager Tanzania Southern Highlands: User Manual - Andersson, Jens; Kilakila, Mukoma Kitundu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Maize-Nutrient-Manager (MNM) gives balanced nutrient and fertiliser mangement advice for one field. Depending on the condition and size of the field, and the money the farmer can invest, it advises what type(s) of fertiliser to use, how much, when, and how best to apply it. MNM generates advice on the basis of three types of information: 1. Field measurement - Using the phone’s in-build GPS, it measures the field on which the farmer plans to grow maize this season; 2. Field conditions - MNM records slope, landscape position, and the oil texture of the field; 3. Field management - MNM records how the field was managed in the past season, recording key information about feriliser and crop management, such the previous crop, the fertiliser types and quantities used, their time of application, and the harvest that the farmer achieved. This information is used to provide the farmer with field-specific advice, tailored to his/her specific field situation and capacity to invest. The user manual is available is English and Swahili